MENINGKATKAN PERILAKU SOPAN SANTUN MELALUI LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK SOSIODRAMA PADA SISWA KELAS IX-F DI SMP NEGERI 2 NALUMSARI - Aditya Septiawan; Gudnanto Gudnanto; Arista Kiswantoro (Jurnal Muria Research Guidance and Counseling (MRGC), 2022)
This  study  aims  to:  (1) describe  the   implementation of groupguidance services with sociodrama techniques to improve polite behavior through group guidance services for students in Class IX-F SMP NEGERI 2 Nalumsari, (2) find out the increase in politeness towards students through group guidance with sociodrama techniques. in grades IX-F at SMP Negeri 2 Nalumsari.The subjects studied were seven out of 31 students of class IX-F SMP Negeri 2 Nalumsari who lacked manners through group guidance using sociodrama techniques. The results showed that using the Group Guidance approach with the Sociodrama technique was proven to improve students' polite behavior with the following details: in the Pre Cycle the achievement was only 40% in the Very Poor category, in Cycle 1 the first meeting achieved 51% in the Less category, Cycle 1 in the third meeting the achievement was 60%.  Poor category, Cycle 2 in the first meeting achieved 69% in the Good category, Cycle 2 in the third meeting achieved 84% in the Very Good category